1986
DOI: 10.1111/j.1651-2227.1986.tb10204.x
|View full text |Cite
|
Sign up to set email alerts
|

Leucocyte Migration Inhibition in Cow's Milk Protein Intolerance

Abstract: The leucocyte migration inhibition (LMI) was determined in an assay after in vitro challenge with beta-lactoglobulin. The assay was considered positive when migration inhibition index was greater than 20% (mean +3 SD of healthy infants). Ninety-eight infants with protracted diarrhoea and failure to thrive, 16 healthy, 12 malnourished, and 16 infants suffering from acute gastroenteritis were studied. Of the 98 patients with protracted diarrhoea, 12 fulfilled Goldman's criteria for cow's milk protein intolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
6
1
Order By: Relevance
“…The results confirmed our original hypothesis in that patients with late reacting CMA show greater evidence of delayed type hypersensitivity (DTH), reflected by LIF production, compared with the other patient groups. Minor et al [8], Khoshoo et al [10] and Ashkenazi et al [9] described similar in-vitro features of DTH to milk proteins in some children with CMA, although their findings are not strictly comparable with the results of this study. Minor et al's [8] patients were older and some had less welldefined symptoms attributable to CMA.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…The results confirmed our original hypothesis in that patients with late reacting CMA show greater evidence of delayed type hypersensitivity (DTH), reflected by LIF production, compared with the other patient groups. Minor et al [8], Khoshoo et al [10] and Ashkenazi et al [9] described similar in-vitro features of DTH to milk proteins in some children with CMA, although their findings are not strictly comparable with the results of this study. Minor et al's [8] patients were older and some had less welldefined symptoms attributable to CMA.…”
Section: Discussioncontrasting
confidence: 67%
“…Both these investigators reported a clear distinction between CMA positive and negative patients in the production of leucocyte migration inhibition factor (LIF). Khoshoo [10], in a study of infants with protracted diarrhoea, demonstrated that the leucocytes of patients with CMPI showed significant migration inhibition after in-vitro incubation with ^-lactoglobulin. In these studies [8][9][10], detailed information regarding the volume of milk administered and the nature or time of onset of symptoms after milk challenge was not described.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports suggest that T-cell mediated reactions play a role in deeluyed reactions to CMP, mainly gastrointestinal and skin reacttions (33). Cellular tests for type IV reactions include in vitro lymphoblast transformation test (172,173), lymphoblastic stimulation test (174,175), and leucocyte migration inhibition test (33,(176)(177)(178)(179). Hill et al (1988) demonstrated an increased production of leucocyte migration inhibitor factor (LIF) in response to ALA, BLG and alpha-CAS in clinically well-defined late reactors, but not in immediate reactors and controls (33).…”
Section: Type IV Cellular Immune Reactionmentioning
confidence: 99%
“…Since its variable symptomatology may render CMAI difficult to diagnose clinically, reliable laboratory methods are required to aid the diagnosis. Prick, scratch and epicutaneous tests, determination of specific IgE antibodies, lymphocyte transformation test, leucocyte migration inhibition assay and histamine release test have been utilized as diagnostic tools in immunologically mediated cow's milk allergy (CMA) [2][3][4][5][6][7][8][9][10][11][12][13][14]. In the present study we used five different in vitro and in vivo tests measuring immediate and delayed responses to CM in 22 children with challenge-proven CMAI.…”
Section: Introductionmentioning
confidence: 99%